2017
DOI: 10.1002/smtd.201600018
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Metal Halide Perovskites: Theory, Synthesis, and Optoelectronics

Abstract: Two‐dimensional (2D) materials attract great attention due to their unique and novel properties in optics, electronics, magnetics, etc. Various 2D materials have been developed since the discovery of graphene, including hexagonal boron nitrides (h‐BNs), transition‐metal dichalcogenides (TMDs), black phosphorus, and so on. Meanwhile, metal halide perovskites are also of great interest because of their high absorbance, high quantum yield, color tunability in the visible‐light range, and high color purity with na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 95 publications
1
100
0
Order By: Relevance
“…The approximate trend of detectivity is similar to the responsivity. From the curves, we can note that the device with ZnO NAs annealed in vacuum shows the highest detectivity, which exceeds 10 14 cm Hz 1/2 W −1 at 450 nm and is comparable to that reported in other papers (see Table 2) [25][26][27].…”
Section: Resultssupporting
confidence: 87%
“…The approximate trend of detectivity is similar to the responsivity. From the curves, we can note that the device with ZnO NAs annealed in vacuum shows the highest detectivity, which exceeds 10 14 cm Hz 1/2 W −1 at 450 nm and is comparable to that reported in other papers (see Table 2) [25][26][27].…”
Section: Resultssupporting
confidence: 87%
“…Reducing number of layers leads to an increase in band gap due to the stronger quantum confinement [82][83][84] and the increase of the exciton binding energy [85]. Recently, 2D and quasi-2D metal halide perovskites received great research attention for their higher stability than their 3D counterparts [86].…”
Section: D and Quasi-2d Metal Halide Hybridsmentioning
confidence: 99%
“…The appealing properties of this new class of materials that might enable advances in electroluminescent devices are their outstanding optical properties including the narrow emission band (<20 nm), a wide wavelength tunability (400-800 nm), and a high PL quantum yield, which make them suitable for high-performance, low-cost, and lightweight LED applications [9][10][11]. Beyond LEDs, they were also explored as interesting materials for low-threshold lasing [12], photodetectors [13], and solar cells [14]. And, many studies on these fields have been reported recently.…”
Section: Introductionmentioning
confidence: 99%